2019
DOI: 10.1002/celc.201901723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrolyte Ions on the Formation, Electroactivity, and Rectification Properties of Films Obtained by Electrografting

Abstract: The oxidation of 4‐(4‐nitrophenyl)butyrate ions in acetonitrile was used to modify glassy carbon surfaces with films bearing 3‐(4‐nitrophenyl)propyl groups. The main features of the voltammetric reduction of the grafted nitrophenyl groups were studied in two different supporting electrolytes; n‐Bu4NPF6 and Me4NPF6. The best response was obtained with the less bulky electrolyte, which was explained by the major capability of these ions to diffuse inside the channels of the grafted film, as well as the better st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Overall, the supporting electrolyte ions, the redox probe and/or the presence of inert additives influence the porous structure of the electrografted film. In a similar context, some evidence about the role of additives and the size of the supporting electrolyte ions on the film permeability, during the electrografting process itself, have been previously reported [31,41] …”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Overall, the supporting electrolyte ions, the redox probe and/or the presence of inert additives influence the porous structure of the electrografted film. In a similar context, some evidence about the role of additives and the size of the supporting electrolyte ions on the film permeability, during the electrografting process itself, have been previously reported [31,41] …”
Section: Resultsmentioning
confidence: 77%
“…Contrasting with these features, the voltammogram of ferrocene on the electrode modified by mediated oxidation of octanoate shows a well‐defined oxidation peak, but without its corresponding reduction peak. This behavior corresponds to a rectification phenomenon, which can also be explained by changes in the mass transport properties inside the film channels (see next section) [30,31] . In this case, mass transport of ferrocene is favored by a higher size of these channels, which are formed during electrografting because of the major number of conformational freedom degrees of the heptyl chains in the polymeric film structure.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Under these conditions, it was impossible to reproduce the behaviour with variations of the transfer coefficient, which indicates that this asymmetry keeps some analogy with that expected for redox probes on partially blocked electrodes, where the peak to peak separation increases by the presence of thin and porous films [16] . Due to this porosity, in some particular cases, this asymmetry could reach a condition where the cathodic current approach a steady state, which is typical of rectification phenomena [13c,16a,17] …”
Section: Resultsmentioning
confidence: 99%
“…Concerning the direct grafting, Guselnikova et al [324] have reported the surface functionalization of a gold substrate by UV-light grafting of the 3,5-bis (trifluoromethyl)phenyl)iodonium salt. Ramírez-Chan et al [325] recently described the fabrication of electrografted films by oxidation of a nitrophenylbutyrate derivative (NO 2 Ph(CH 2 ) 3 COO − ) exploring the influence of different supporting electrolyte ions on the film formation. Madsen et al [326] used a two-phase bipolar grafting system to simultaneously functionalize gold bipolar electrodes with diazonium salts and primary amines or thiophenes.…”
Section: The Electrografting Techniquementioning
confidence: 99%